Profoundly Understanding Marketing 4.0 - วงษ์มณฑา เสรี (Journal of Industrial Business Administration, 2019)
Marketing 4.0 is an expansion of Marketing 3.0 with conspicuous transformation. It is the integration between traditional marketing and digital marketing. It deploys creativity and technology to come up with innovative values for consumers 4.0 who are natives of Digital Nation. Marketing 4.0 comprises of several marketing strategies on social media; thus, entrepreneurs must develop competency in social marketology. The most important issue is Marketing 4.0 is Mission Marketing to create values for consumers regardless whether they are customers or non-customers. It requires that entrepreneurs uphold governance principles with commitments to make human lives better and to promote sustainability. It aims at building charismatic brands with CSR programs.